UPM receives Graduates’ Choice Award (GCA) 2023 - Mohd Azhari, Nurul Ezzaty (Pusat Strategi dan Perhubungan Korporat, Universiti Putra Malaysia, 2023)
SUBANG JAYA, Jan 5 - Universiti Putra Malaysia (UPM) has received the Graduates’ Choice Award (GCA) 2023 under the public universities (UA) category by Talentbank as an employer of choice among undergraduates.